2000
DOI: 10.4269/ajtmh.2000.62.277
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion envenomation and serotherapy in Morocco.

Abstract: Abstract.A clinical and biologic study was conducted in Morocco to assess the efficiency of antivenom therapy for treating victims of scorpion stings. Epidemiologic and clinical data were collected from 275 patients envenomed by Androctonus mauretanicus mauretanicus and Buthus occitanus scorpions. Patients received antivenom or other drugs. Blood samples were collected at the time of hospital admission and 1 hr and 3 hr after treatment. Serum venom levels were quantified by using an ELISA. An association was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 33 publications
7
54
0
3
Order By: Relevance
“…Using the ELISA described here, we have also measured a similar venom level (67.8 ng/ mL) in a fatal case of a 4-year-old boy bitten by a Phoneutria spider in the southern Brazilian state of Santa Catarina (unpublished case attended at the State Poison Control Center of Santa Catarina, in Florianópolis, SC, Brazil). Although the venom level observed in our case was higher than those reported by Chávez-Olórtegui et al (22), it was nevertheless compatible with that reported for other arachnids, particularly scorpions such as Androctonus mauretanicus mauretanicus and Buthus occitanus (venom levels 15.9-49.7 ng/mL) (27), Androctonus australis (venom levels 17-29 ng/mL) (28), and Tityus serrulatus (venom levels 4.0-50.0 ng/mL) (29).…”
Section: F Bucaretchi Et Alsupporting
confidence: 90%
“…Using the ELISA described here, we have also measured a similar venom level (67.8 ng/ mL) in a fatal case of a 4-year-old boy bitten by a Phoneutria spider in the southern Brazilian state of Santa Catarina (unpublished case attended at the State Poison Control Center of Santa Catarina, in Florianópolis, SC, Brazil). Although the venom level observed in our case was higher than those reported by Chávez-Olórtegui et al (22), it was nevertheless compatible with that reported for other arachnids, particularly scorpions such as Androctonus mauretanicus mauretanicus and Buthus occitanus (venom levels 15.9-49.7 ng/mL) (27), Androctonus australis (venom levels 17-29 ng/mL) (28), and Tityus serrulatus (venom levels 4.0-50.0 ng/mL) (29).…”
Section: F Bucaretchi Et Alsupporting
confidence: 90%
“…While several authors argue that a correct clinical management of Buthidae envenomation treatment eliminates the need for specific antivenom (3,(36)(37)(38), other authors recommend the use of scorpion antivenom (5,8,14,(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…anos, sendo atribuídos à proporção de veneno inoculado em relação à superfície corpórea, com níveis séricos conseqüen-temente mais elevados 21 …”
Section: Introductionunclassified